A pH-responsive bi-MIL-88B MOF coated with folic acid-conjugated chitosan as a promising nanocarrier for targeted drug delivery of 5-Fluorouracil - Akbar, Muhammad Usman; Khattak, Saadullah; Khan, Malik Ihsanullah; Saddozai, Umair Ali Khan; Ali, Nemat; AlAsmari, Abdullah F.; Zaheer, Muhammad; Badar, Muhammad (Frontiers in Pharmacology, 2023)
Cancer has remained one of the leading causes of death worldwide, with a lack of effective treatment. The intrinsic shortcomings of conventional therapeutics regarding tumor specificity and non-specific toxicity prompt us to look for alternative therapeutics to mitigate these limitations.The intrinisic shortcomings of the conventional therapeutics in terms of tumor spcecificity and non-specicfic toxicity prompts to look for alternative therapeutics mitigate these limitations. In this regard, we developed multifunctional bimetallic (FeCo) bi-MIL-88B-FC MOFs modified with folic acid -conjugated chitosan (FC) as drug delivery systems (DDS) for targeted delivery of 5-Fluorouracil (5-FU). The bi-MIL-88B nanocarriers were characterized through various techniques, including powder X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray, thermogravimetric analysis, and Fourier transform infrared spectroscopy. Interestingly,